Cutting through: How to address the cost of living crisis - Matthew Lesh; Kristian Niemietz (Institute of Economic Affairs (IEA), 2022)
The cost-of-living crisis has been worsened by longer-term structural factors, beyond the immediate issues posed by loose monetary policy and supply-side constraints. Indeed, there were discussions about a cost-of-living crisis over a decade ago, long before Covid, the Ukraine war or Brexit.The British state intervenes heavily in various product markets through tax and regulatory measures, in ways which drive up costs. Some of those interventions may be justified (e.g. to correct externalities), but in many cases the costs imposed on consumers are substantial, while the benefits are either trivial or highly speculative.Childcare costs in the UK have risen to one of the highest levels in the developed world. This is in large part due to stringent minimum staff-to-children ratios, the imposition of a 'curriculum', accreditation costs and, more generally, over-formalisation of the sector.Relaxing childcare sector regulatory requirements does not have to mean complete deregulation. It could merely mean bringing them more into line with what is standard practice in many European neighbour countries. This could cut costs by around 40 per cent, or over 300 per child and per month.The ratio of median house prices to median gross full-time annual earnings has gone up from under 4 in the late 1990s to over 9 today. Rents in UK towns and cities are among the highest in the developed world. Renting a flat in Oxford, for example, is more expensive than renting a comparable flat in Berlin, Vienna, Rome or Brussels.There is a wealth of empirical evidence which shows that the severity of land use planning restrictions is a key determinant of housing costs. Easing restrictions in such a way that housing costs could fall back into line with the historic norm would imply a drop by at least 40 per cent. Median private sector rents in England could fall by over 250 per month.Paternalistic 'nanny-state' taxes cost a moderate smoker and drinker about 140 a month. These taxes could be cut back to a realistic estimate of the external costs imposed on others by those activities.Excessive occupational licensing rules and immigration restrictions raise consumer prices without a detectable increase in the safety or quality of the affected services.The UK should unilaterally abolish tariffs, and automatically recognise regulatory standards from countries where those standards can be reasonably expected to be equivalent to domestic ones.The UK has chosen an inefficient, unnecessarily costly decarbonisation strategy, which drives up energy costs for households and businesses by more than what is required in order to reduce CO2 emissions. The government should phase out renewable energy subsidies, bring carbon pricing into line with the EU average, allow the hydraulic fracturing ('fracking') of shale gas, and remove obstacles to investment in North Sea oil.
Keywords: 330